2016
DOI: 10.1039/c5mb00804b
|View full text |Cite
|
Sign up to set email alerts
|

Probing fatty acid metabolism in bacteria, cyanobacteria, green microalgae and diatoms with natural and unnatural fatty acids

Abstract: In both eukaryotes and prokaryotes, fatty acid synthases are responsible for the biosynthesis of fatty acids in an iterative process, extending the fatty acid by two carbon units every cycle. Thus, odd numbered fatty acids are rarely found in nature. We tested whether representatives of diverse microbial phyla have the ability to incorporate odd-chain fatty acids as substrates for their fatty acid synthases and their downstream enzymes. We fed various odd and short chain fatty acids to the bacterium Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…Primary role of fatty acids is to act as the hydrophobic component of the membrane lipids in both eukaryotes and prokaryotes [ 33 ]. Fatty acid synthases are responsible for the biosynthesis of fatty acids, extending its length by two carbon units every cycle [ 41 ]. Meanwhile, some of the intermediate metabolites are important precursors for synthesis of many bioproducts [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary role of fatty acids is to act as the hydrophobic component of the membrane lipids in both eukaryotes and prokaryotes [ 33 ]. Fatty acid synthases are responsible for the biosynthesis of fatty acids, extending its length by two carbon units every cycle [ 41 ]. Meanwhile, some of the intermediate metabolites are important precursors for synthesis of many bioproducts [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Synechocystis genome encodes no proteins with homology to enzymes involved in β-oxidation (Supplementary Table S2), although one report has suggested that the capacity for fatty acid catabolism is retained [138]. If so, there must be an alternate, uncharacterized pathway responsible for lipid degradation.…”
Section: Lipid Biosynthesismentioning
confidence: 99%
“…We envisioned that an apparent inability of cyanobacteria to carry out canonical beta-oxidation of FAs coupled to the capacity to elongate exogenously-supplied FAs 31,32 would allow for extensive labeling of their FA-derived lipidome ( Fig. 1a) using stable-isotope labeled-precursors (as observed by Burkart et al 31 in Synechocystis sp. PCC 6803).…”
Section: Ms-guided Isolationmentioning
confidence: 99%